Production of cellobiose from the partial enzymatic hydrolysis of rice husk cellulose - Ayala Armijos, Humberto (2024)
The aim of the research was to soften rice husk by hydrothermal and alkaline pretreatments. Temperature was applied at 121 °C for three time periods (15, 30 and 45 minutes) and with NaOH in three concentrations (0,5, 1 and 1,5 %), it was stirred at 120 rpm for one hour, to adjust to pH 4,8; 20 % HCl was added, and 30 FPU of the enzyme β-glucosidase was added and stirred at 120 rpm at 50 °C for 144 hours. The application of 121 °C for 45 minutes achieved a 34,62 ± 0,79 % partial hydrolysis of cellulose to cellobiose and 18,14 ± 0,09 % total hydrolysis of cellulose to glucose and in the hydrolysates where it was pretreated with sodium hydroxide at 1,5 %, 8,39 ± 0,79 % cellobiose and 46,64 ± 0,30 % glucose were reached. The application of hydrothermal pretreatment favors the partial hydrolysis of cellulose to cellobiose.